CREATIVITY IN PROFESSION OF TEACHER - KRIZOVSKA, Ilona (Trends in education, 2008)
The article presents creativity in profession of teacher, it extasciiacutes assertion in the education. There are presented some changes in profession of teacher in the view of social meaning, the problems connected with it, which has influence on creative manifestation.
Keywords: creativity; profession of teacher; education